Enhancing pre-trained language model by answering natural questions for event extraction - Zhang, Yuxin; Han, Qing (Frontiers in Artificial Intelligence, 2025)
IntroductionEvent extraction is the task of identifying and extracting structured information about events from unstructured text. However, event extraction remains challenging due to the complexity and diversity of event expressions, as well as the ambiguity and context dependency of language.MethodsIn this paper, we propose a new method to improve the precision and recall of event extraction by including topic words related to events and their contexts, directing the model to focus on the relevant information, and filtering the noise.ResultsThis method was evaluated on the ACE 2005 dataset, achieving an F1-score of 77.27% with significant improvements in both precision and recall.DiscussionOur results show that the use of topic words and question answering techniques can effectively address the challenges faced by event extraction and pave the way for the development of more accurate and robust event extraction systems.